Review: nutritional requirements of Pimelodidae fishes in South America (Teleostei: Siluriformes) - Gutiérrez Espinosa, Mariana Catalina; Velasco Garzón, Juan Sebastian; León Morales, Carlos Arturo (Revista de Biología Tropical, 2019)
The Silurids, also known as catfish is one of the most representative groups of fish. Comprised of 31 families, 412 genera and approximately 2 600 species, which places them, as the third among all orders of teleost of which 13 families (64 % of the species) living in South America. Within this order is the Pimelodidae, Eigenmann and Eigenmann family (1889), the most abundant in Neotropical siluriformes widely distributed in South and Central America. Some representatives of the Pimelodidae family are individuals whose specific characteristics make capable of being handled in captivity for commercial purposes. One of the main negative factors for profitable business is the lack of knowledge about, among other things, the basic elements to formulate well-balanced diets and to provide the fish with their basic nutritional requirements for an optimal development. For this reason, it is of paramount importance to make a general bibliography review of the main aspects related to food and nutrition of the family.